2005
DOI: 10.1203/01.pdr.0000150726.75308.22
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Decreases Surfactant Inactivation In Vitro

Abstract: Hyaluronan (HA) is an anionic polymer and a constituent of alveolar fluid that can bind proteins, phospholipids, and water. Previous studies have established that nonionic polymers improve the surface activity of pulmonary surfactants by decreasing inactivation of surfactant. In this work, we investigate whether HA can also have beneficial effects when added to surfactants. We used a modified pulsating bubble surfactometer to measure mixtures of several commercially available pulmonary surfactants or native ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 35 publications
4
45
1
4
Order By: Relevance
“…chitosan and HA). For instance, addition of 2.5 mg/mL HA to 0.5 mg/mL BLES impairs adsorption; however, previous studies showed that 2.5 mg/mL HA improved the surface activity of 1.25 mg/mL therapeutic surfactants (10,11), i.e. at a concentration higher than the BLES concentration in the present study.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…chitosan and HA). For instance, addition of 2.5 mg/mL HA to 0.5 mg/mL BLES impairs adsorption; however, previous studies showed that 2.5 mg/mL HA improved the surface activity of 1.25 mg/mL therapeutic surfactants (10,11), i.e. at a concentration higher than the BLES concentration in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…More recently, Lu et al (10,11) reported the use of an anionic polymer, HA, as a surfactant additive. Both in vitro (10) and in vivo (11) tests showed that the addition of HA at different molecular weights to various therapeutic lung surfactants can effectively reverse serum-and meconium-induced inactivation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple reports indicate improved surfactant function when polymers such as dextrans, PEG, and hyaluronan are added to surfactant preparations in vitro (12)(13)(14)(15). Animals with ALI have improved lung function when treated with surfactant polymer mixtures versus surfactant alone.…”
mentioning
confidence: 99%